Detection of colistin-resistant Escherichia coli isolated from broiler chickens in Kelantan, Malaysia - Devan, S. S.; Aklilu, E.; Hamdan, R. H.; Lemlem, M.; Zakaria, Z. (Malaysian Society of Parasitology and Tropical Medicine, 2022)
Antimicrobial resistant Escherichia coli have become an ever increasing problem in human, and animal health and production. The imprudent use of antibiotics and poor hygienic practices especially in poultry industries have been contributing to the emergence and spread of E. coli species resistant to broad spectrum antibiotics including Colistin. This study was conducted to detect colistin – resistance and antibiotic sensitivity patterns in E. coli isolated from broiler chickens in Kelantan. A total of 320 cloacal swabs were collected from apparently healthy broiler chickens in different districts of Kelantan and were analysed using routine microbiological methods, Kirby–Bauer method for antimicrobial susceptibility test and PCR amplification of species-specific and colistin - resistance encoding genes. Out of the 320 samples, 91 isolates were confirmed as E. coli and 21/91 (23.08%) were positive for colistin - resistant encoding gene, mcr-1. Most of the isolates were resistant to tetracycline (95.24%), chloramphenicol (85.71%), and sulphamethoxazole/ trimethoprim (85.71%). However, the isolates were less resistant towards piperacillin/ tazobactam (4.76%) and meropenem (9.52%). The findings from this study reveal the emerging threats of colistin - resistant in local food animal production, particularly in poultry production industry. However, more comprehensive, and large-scale studies focusing on more resistance patterns using determination of minimum inhibitory concentration (MIC), virulence and resistance characteristics and molecular epidemiology of colistin – resistant E. coli are recommended for better understanding of the epidemiology and to implement the appropriate control and prevention strategies.